2018
DOI: 10.15421/191805
|View full text |Cite
|
Sign up to set email alerts
|

How can assessment systems be used to evaluate healthcare activities in the care farms?

Abstract: Purpose – to identify in the literature the main activities of Social Agriculture and elaborate a framework easily readable to manage them. Design/Method/Approach –systematic literature review. Findings. Formulation of an interpretative framework for evaluation and management of the existing Social Agriculture actions trough a system-describing pattern. Theoretical implications. Care farms are the most innovative expressions of the agriculture multifunctional. Through the development of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…There is growing evidence that being exposed to nature, whether it is in the countryside, forests, street trees, allotments, or gardens, can have a positive impact on a person's health [115][116][117]. In the last decades, the European Union has been focusing on promoting multifunctional farming practices that combine agriculture with therapy and alternative ways to help people in difficult situations [118]. Several studies [119][120][121][122] have shown that contact with nature can improve psychological health by reducing stress levels, enhancing mood, and providing a restorative environment.…”
Section: Green Care and Therapy Farm Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that being exposed to nature, whether it is in the countryside, forests, street trees, allotments, or gardens, can have a positive impact on a person's health [115][116][117]. In the last decades, the European Union has been focusing on promoting multifunctional farming practices that combine agriculture with therapy and alternative ways to help people in difficult situations [118]. Several studies [119][120][121][122] have shown that contact with nature can improve psychological health by reducing stress levels, enhancing mood, and providing a restorative environment.…”
Section: Green Care and Therapy Farm Initiativesmentioning
confidence: 99%
“…Social farming is an innovative approach that benefits public health and improves social health status [127]. It has become a popular practice recently, especially for those with behavioral or health issues [118]. The concept of using farms for green care has evolved over time.…”
Section: Green Care and Therapy Farm Initiativesmentioning
confidence: 99%